PENGEMBANGAN MEDIA INTERAKTIF BERBASIS GOOGLE SITES UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V SEKOLAH DASAR - Erika Safitri; Sri Cacik (Prodi PGSD Universitas PGRI Ronggolawe, 2023)
This study aims to develop a product in the form of google sites-based interactive media for grade V science content. In developing google sites-based interactive media, it is necessary to test the validity, effectiveness, and practicality to determine the quality of the learning media that has been developed. The method used in interactive media development research based on google sites is the ADDIE model, namely Analysis, Design, Develop, Implement, and Evaluate. Media validation results for 3 expert validators, namely media experts obtained an average of 93%, material experts obtained an average of 92% and linguists obtained an average of 90% so that the media was declared valid. The results of practicality assessed by assessors obtained results of 91% and student responses obtained by 95% so that Interactive media was stated to be very practical. based on the google site declared effective. From the results of this study it can be concluded that the development of Google site-based interactive media can affect the improvement of student learning outcomes.